Fortifying federated learning: security against model poisoning attacks - Anan, Fabiha; Mamun, Kazi Shahed; Kamal, Md Sifat; Ahsan, Nizbath (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.